2018
DOI: 10.1172/jci120391
|View full text |Cite
|
Sign up to set email alerts
|

Effective NY-ESO-1–specific MHC II–restricted T cell receptors from antigen-negative hosts enhance tumor regression

Abstract: Adoptive transfer of T cell receptor-engineered (TCR-engineered) T cells is a promising approach in cancer therapy but needs improvement for more effective treatment of solid tumors. While most clinical approaches have focused on CD8 + T cells, the importance of CD4 + T cells in mediating tumor regression has become apparent. Regarding shared (self) tumor antigens, it is unclear whether the human CD4 + T cell repertoire has been shaped by tolerance mechanisms and lacks highly functional TCRs suitable for thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…Moreover, as engineered TCRs are traditionally designed based on reactivity to a single dominant epitope of a tumor antigen, TCRs with reactivity to subdominant epitopes of tumor antigens remain conspicuously unexplored. Even in the case of Poncette et al, while they confirmed natural processing of NY-ESO-1 116-135 by immunizing mice with full-length NY-ESO-1 DNA, they required that all of their TCRs stain positive for DR4/NY-ESO-1 116-135 tetramer (9). In the process, however, they may have screened out TCRs that target different portions of the NY-ESO-1 protein but still have potent antitumor activity.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Moreover, as engineered TCRs are traditionally designed based on reactivity to a single dominant epitope of a tumor antigen, TCRs with reactivity to subdominant epitopes of tumor antigens remain conspicuously unexplored. Even in the case of Poncette et al, while they confirmed natural processing of NY-ESO-1 116-135 by immunizing mice with full-length NY-ESO-1 DNA, they required that all of their TCRs stain positive for DR4/NY-ESO-1 116-135 tetramer (9). In the process, however, they may have screened out TCRs that target different portions of the NY-ESO-1 protein but still have potent antitumor activity.…”
Section: Discussionmentioning
confidence: 98%
“…These TCRs were shown to recognize NY-ESO 116-135 -loaded, NY-ESO-1-transduced, and naturally expressing NY-ESO-1 melanoma cell lines more effectively than the ones isolated from human CD4 + T cells. Moreover, their EC 50 values in a NY-ESO-1 peptide titration assay were almost a log-fold lower than 3 of 5 human-derived TCRs (10 -10 vs. 10 -9 M), they secreted greater maximal IFN-γ concentrations, and they had higher MFIs when stained with DR4/ NY-ESO-1 116-135 tetramer (9). One TCR, TCR-3598_2, was chosen for a combined CD4 + and CD8 + ACT study, as it showed no signs of alloreactivity or crossreactivity with any other naturally processed and presented human self-peptides that contain its recognition motif (9).…”
mentioning
confidence: 94%
See 3 more Smart Citations